PERAN KEJAKSAAN DAN PERAN JAKSA PENUNTUT UMUM DALAM PENEGAKAN HUKUM - Imman Yusuf Sitinjak (LP2MTBM MAKARIOZ, 2018)
Writing this paper aims to determine the role of the prosecutor and public prosecutors in law enforcement. Writing this paper uses the method of literature review (library research) based on expert opinions and research journals that support the topic of this paper. From the discussion it can be concluded that the actions carried out by the public prosecutor in the process of prosecution and prosecution are actually carried out on the basis of justice and truth based on the Almighty Godhead. Law enforcement for the sake of justice also includes fairness to the accused, fair to the people who affected by the actions of the defendant and fair in the eyes of the law, thus automatically what is done by the public prosecutor in the context of law enforcement is to achieve the legal objectives of legal certainty, bridging a sense of justice and legal benefit for justice seekers.